CARISSA EDULIS PHYTOCHEMICAL AND PHARMACOLOGICAL STUDIES: A REVIEW ARTICLE - TOKOUDAGBA, Kossi Jean-Marie Denis; Houngue, Ursula (My University, 2022)
Carissa edulis is a plant of Apocynaceae family that is used in many countries of Africa, Asia, and Oceania. The plant has been employed and used in traditional medicine for various ailments. The diversified utilizations, widely acclaimed and proven efficacy of preparations of C. edulis in traditional medicine have led researchers to take an interest in phytochemical and pharmacological properties of this plant. Objective: The purpose of this review isto provide updated information about therapeutic effects of C. edulis and improve our future experimental and clinical research plan. Methods: This review covers articles between 1975 and 2020. The available information was collected via electronic search (Pubmed, SciFinder, Google Scholar, ResearchGate) and a library search for articles published in peer-reviewed journals, using ‘‘Carissa edulis’’ as search term (‘‘all fields’’) and with no specific time frame set for search. No restrictions regarding the language of publication were imposed. Results: Studies have shown that extracts of C. edulis may contain biologically active principles with diuretic, analgesic, antimicrobial, antidiabetic and anticancer effects. It’s a plant with many properties that is rich in flavonoids, phenolic compounds, chlorogenic acid derivatives, lignans, sesquiterpene, sterols, triterpenes, coumarins, cardiac glycosides and miscellaneous compounds. Though short term used of the plant doesn’t have any toxic effect, its long term used can alter hepatic, renal and haematopoietic functions of the organism. Conclusion: Although the mechanisms of action are not very clear, there is enough evidence of C. edulis efficacy in the treatment of many diseases. However, it’s necessary to do more well-designed animal and randomized clinical studies with sufficient sample sizes, to collect more objective data and confirm traditional effects of this plant. Exploring other fields of research such as the effect of the plant on cardiovascular disease would also be interesting
Keywords: Carissa edulis; traditional medicine; therapeutic effects.